2018
DOI: 10.5194/angeo-36-405-2018
|View full text |Cite
|
Sign up to set email alerts
|

Report of a large depletion in the ozone layer over southern Brazil and Uruguay by using multi-instrumental data

Abstract: Abstract. Ozone is one of the chemical compounds that form part of the atmosphere. It plays a key role in the stratosphere where the “ozone layer” is located and absorbs large amounts of ultraviolet radiation. However, during austral spring (August–November), there is a massive destruction of the ozone layer, which is known as the “Antarctic ozone hole”. This phenomenon decreases ozone concentration in that region, which may affect other regions in addition to the polar one. This anomaly may also reach mid-lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
(21 reference statements)
0
8
0
3
Order By: Relevance
“…To exemplify the analysis developed in this paper, we present in the next section a case study that took place on 18 September 2017, as this is the most recent event identified throughout the observed period, showing a side-effect event of AOH in the region of southern Brazil. Other interesting, and even more prominent, events have already been reported by Bresciani et al (2018) and Bittencourt et al (2018).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…To exemplify the analysis developed in this paper, we present in the next section a case study that took place on 18 September 2017, as this is the most recent event identified throughout the observed period, showing a side-effect event of AOH in the region of southern Brazil. Other interesting, and even more prominent, events have already been reported by Bresciani et al (2018) and Bittencourt et al (2018).…”
Section: Resultsmentioning
confidence: 61%
“…For this analysis, one needs to consider the previous days of the event or equatorial origin when a decrease in absolute potential vorticity occurs (Semane et al, 2006). Bittencourt et al (2018) and Bresciani et al (2018) showed the analysis of an extreme event of influence of the AOH on regions of middle latitudes through the analysis of the stratospheric dynamics with the fields of PV.…”
Section: Identification Of Aoh Influence Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most production takes place in the mesospheric-stratospheric equatorial region due to the higher level of solar radiation, the maximum ozone concentration is observed over the polar region (Salby, 1996). This zonal distribution is explained by the Brewer-Dobson circulation (Brewer, 1949;Dobson, 1956), which transports ozone-rich air masses from the Equator to the pole and into the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was first observed by Kirchhoff et al (1996) and reported by Pinheiro et al (2011) in South America. Recently, based on satellite and ground-based observations in Uruguay and southern Brazil, Bresciani et al (2018) showed a decrease in ozone over these sites during October 2016 due to the influence of the AOH reaching mid-latitudes. The air-mass transport in the stratosphere has been extensively analysed using the advected potential vorticity (APV), which is considered a suitable dynamical tracer in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%